An Evaluation of Dana Gas’s Mudarabah Sukuk from Shariah and Legal Perspectives - Hekmatyar, Muhammad Salahuddin; Parkar, Ebrahim (European Journal of Islamic Finance, 2018)
Dana Gas’s proclamation that its sukuk is unlawful under Shariah and UAE law, garnered the attention of prominent business publications in the summer of 2017. The unprecedented move by Dana Gas could potentially instigate wider ramifications for the sukuk industry. The purpose of this paper, is to investigate whether Dana Gas provided valid grounds to justify their sukuk as being unlawful under Shariah law. It highlights the key claims of Dana Gas about the prevailing market conditions at the time of the sukuk issuance and the legal challenges involved. The methodological approach of this paper focuses on key documentation, which includes the sukuk prospectus and company statements. Based on the analysis of the sukuk features, there are a few infringements of Shariah rulings in the profit distribution and purchase undertaking practices, when benchmarked against AAOIFI (Accounting and Auditing Organization for Islamic Financial Institutions) standards.